Avaliação do disclosure de sustentabilidade nas cooperativas agropecuárias no Paraná - Giasson, Oldair Roberto (2021)
Sustainability has gone from being a passing trend or a popular slogan to effectively embodying the operations, businesses and strategies of organizations around the world. This change is being driven by the pressures received from stakeholders, linked to organizations, that provide this transformation. This paper analyzes the issues surrounding sustainability in the disclosure assessment segment in agricultural cooperatives, considering that these organizations have a large representation in Paraná agribusiness and are responsible for the income of many agricultural producers, their employees and the development of local communities. As for the theoretical implications, the work contributes to the assessment of sustainability disclosure, within sustainable operations, as for the practical implications, it demonstrates the assessment process, the procedures for data collection and analysis, the lessons learned and the use of the assessment method disclosure in cooperatives. Thus, the main objective of this work is to evaluate the disclosure of sustainability in agricultural cooperatives, in Paraná, in order to identify the reasons and advantages that this action can provide. As a research technique, bibliographic research with content analysis was used to identify the state of the art of sustainability issues incorporated into the operations of the respective cooperatives. Procedures related to the analysis of management reports, statistical analysis, use of the case study methodology in some cooperatives, document analysis and interviews with managers in the strategic and operational area were also used. The information obtained was analyzed using a quantitative and qualitative approach (combined), highlighting the aspects of management and sustainability and the operations of the entities. The results of the cluster analysis survey identified that, of the 13 cooperatives analyzed in the period 2010 to 2018, two groups were formed, one with the cooperatives that performed as expected and the other with the cooperatives that had the result below expected. It was observed that cooperatives do not have a standard in the disclosure of sustainability information in their respective annual reports and, following the information collected in the interviews, this is due to the lack of a formalized policy by OCEPAR for cooperatives to disclose their reports on their websites and also to highlight sustainability aspects. Even with the formation of two distinct groups, these do not present significant differences in their accounting and financial indicators, except in the billing, asset size, indebtedness and liquidity indicators. Despite the low number of cooperatives that publish their annual reports on their respective websites, in this study 13 cooperatives in a universe of 59 agricultural cooperatives linked to OCEPAR, it can be considered a representative result, as these organizations are considered the largest in our country. The suggestion for future research contemplates a broader study, considering the assessment of sustainability disclosure in other organizations, both in Paraná and in the Brazil, as a whole, seeking to identify the advantages that each cooperative could obtain in carrying out and show more aspects of sustainability.